Penerapan Algoritma Minimax Pada Game Macan-macanan - Santoso, Kartika Imam; Yunita, Farida; Kusumo, Nafi Projo (Universitas Diponegoro, 2016)
Lots of traditional games, but now the game is becoming obsolete. Many games were replaced with the modern game technology products. Modern games are becoming more practical because it did not require the terrain and many friends. Quite alone in front of the screen was a person may engage in an exciting game. One of the efforts to preserve and disseminate traditional games one of which is macan-macanan is to adapt the game into a computer game. This study aims to apply artificial intelligence using minimax algorithms and programming language ActionScript 3 in the game with a macan-macanan research methods are prototyping. The design used in this study is an artificial intelligence approach for representing the state, science, human computer interaction for designing the user experience, as well as the UML for object-based design. Results from this study is that in order to determine the value of the evaluation algorithm minimax for the end node / terminal state in the game macan-macanan, required the calculation of the total step is valid for each piece, as well as to pawn macan, necessary calculations springboard to a higher value and the weight difference the appropriate type of pawns.